3D‐Graphene Decorated with g‐C3N4/Cu3P Composite: A Noble Metal‐free Bifunctional Electrocatalyst for Overall Water Splitting. Issue 5 (17th January 2020) - Riyajuddin, Sk.; Tarik Aziz, S. K.; Kumar, Sushil; Nessim, Gilbert D.; Ghosh, Kaushik
Abstract: Electrochemical water splitting, which generates both hydrogen and oxygen, using highly efficient and low‐cost noble metal‐free (Pt, Ru, Ir etc.) electrocatalyst is an economical and green approach for the alternative energy source. Due to their conductivity, durability and long‐term stability, carbonaceous containing hybrid materials are used as promising electrodes for total water splitting. Herein, the design of metal‐phosphide (Cu3 P) with graphitic carbon‐nitride (g‐C3 N4 ) nanocomposite on 3D‐graphene is reported, a new model electrocatalyst that in turn, render superior electrocatalytic performance with long‐term stability. The excellent electrocatalytic performance is analyzed in terms of overpotentials of 67 mV and 255 mV at a current density of 10 mA/cm 2 with a small Tafel slope of 45 and 40 mV/dec for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), respectively. The overall water splitting performance has been tested in 1 M KOH electrolyte, and the catalyst exhibits a very low cell voltage of 1.54 V to achieve a current density of 10 mA/cm 2 with impressive stability of at least 35 hours with no loss of potential. This work sheds new insight into the design and synthesis of highly stable electrocatalyst that could be an apt choice for an attractive paradigm for commercial water electrolysis in renewable electrochemical energy conversion. Abstract : Water splitting : Graphitic carbon nitride (g‐C3 N4 ) and Copper phosphide (Cu3 P) are decorated on highly pours 3D‐Graphene matrix. This nano composite(3D‐Graphene‐g‐C3 N4 /Cu3 P) work as an efficient bifunctional electrocatalyst for overall water splitting.